The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.18231/j.ijca.2021.088
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the perfomance between I-gel® and Classic laryngeal mask airway in anaesthetized spontaneously breathing patients

Abstract: The classic Laryngeal Mask Airway (c-LMA) is a first generation supraglottic airway device with an inflatable cuff forming a low pressure seal around the laryngeal inlet and permitting ventilation. I-gel is a supraglottic airway device made of thermoplastic elastomer which is soft gel-like and transparent. Unlike the classic LMA(c-LMA), I-gel does not have an inflatable cuff. In view of this, the present study was undertaken to compare the performance of the two supraglottic airway devices in spontaneously br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Jacob et al observed I-gel had a lower incidence of complications such as cough, sore throat, blood staining, etc. 9 Similarly, we found sore throat and hoarseness of voice after 24 hours of surgery was more in C-LMA than I-gel, but was statistically non-significant (p>0.05).…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Jacob et al observed I-gel had a lower incidence of complications such as cough, sore throat, blood staining, etc. 9 Similarly, we found sore throat and hoarseness of voice after 24 hours of surgery was more in C-LMA than I-gel, but was statistically non-significant (p>0.05).…”
Section: Discussionmentioning
confidence: 54%
“…It was highly significant, with a p value of <0.001. 9 In study by Gupta et al the mean inserting time was shorter for I-gel (11.07±1.93 seconds) than LMA (12.50±2.35 seconds) and the difference was statistically significant. 4 We found mean number of attempts of successful insertion was 1.11±0.32 times in C-LMA group and 1.03±0.17 times in I-gel group, which was statistically non-significant (p>0.05).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations